2006
DOI: 10.1007/s00484-006-0030-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of evaporative cooling on reproductive performance and milk production of dairy cows in hot wet conditions

Abstract: Fourteen animals of second and third lactation of Thai Friesian crossbred cows (87.5% Friesian x 12.5% Bos indicus) located at Sakol Nakhon Research and Breeding Centre, Department of Livestock Development, Ministry of Agriculture and Cooperatives, were divided randomly into two groups of seven each to evaluate the effects of evaporative cooling on reproductive and physiological traits under hot, humid conditions. Results indicated that installation of evaporating cooling in the open shed gave a further improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Our findings on CR (68.75% and 33.33% in shortterm cooled and control groups, respectively) are in consonance with the results (71.43% and 14.29% in evaporately cooled and non-cooled cows, respectively) reported by Khongdee et al (2006). Similar findings were also reported by Moghaddam et al (2009), who observed higher CRs (40-56.7%) in cooled compared to non-cooled (23.3%) Holstein heifers.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our findings on CR (68.75% and 33.33% in shortterm cooled and control groups, respectively) are in consonance with the results (71.43% and 14.29% in evaporately cooled and non-cooled cows, respectively) reported by Khongdee et al (2006). Similar findings were also reported by Moghaddam et al (2009), who observed higher CRs (40-56.7%) in cooled compared to non-cooled (23.3%) Holstein heifers.…”
Section: Discussionsupporting
confidence: 81%
“…The heifers in short-term cooled group had lower body temperature compared to those in control group indicating that this method is efficient in maintaining normal body temperature around the time of AI. Earlier reports also suggest that cooling methods like wallowing, intermittent splashing of water (Singh et al 2005), evaporative cooling (Khongdee et al 2006;Moghaddam et al 2009) and direct watering with forced ventilation (Flamenbaum & Galon 2010) had ameliorative effect on rectal and body temperature. It has been reported that under thermal stress the blood flow in female animals increased in the proximity of the superficial vessels in detriment of the deep vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by other Authors in analogous climate conditions when cows were cooled by evaporative cooling systems installed in the resting area (Khongdee et al, 2006;Calegari et al, 2012).…”
Section: Articlesupporting
confidence: 90%
“…In general, spray cooling and evaporative cooling are dependent on the moisture holding capacity of ventilation air, but even humid environments can benefit (Table 3 in Hahn and Osburn 1969). Khongdee et al (2006) have shown specific benefits for dairy cows in hot humid conditions. Tunnel ventilation systems, characterized by a bank of fans on one end of the building with inlets on the opposite end, are designed to achieve a specific air speed to optimize convective heat loss (Gooch and Stowell 2003;Bray et al 2003).…”
Section: Management Practicesmentioning
confidence: 99%